The relationship between traditional bullying/cyberbullying with resilience, anxiety and depression in adolescents (Annals of Medical Research, 2022)
Aim: Both bullying and victimization are a serious negative life experience for children and adolescents and the effects are not limited to the period of bullying, but may last for a lifetime and negatively affect the mental health. In this study, we aimed to investigate the frequency of bullying and victimization of adolescents-both traditional and cyber- and to determine their relationship with resilience, anxiety and depression.Materials and Methods: This study was carried out online with 207 adolescents. The participants filled the demographic data form, Bullying and Cyberbullying Scale for Adolescents, Adolescent Psychological Resilience Scale (APRS), DSM-5 Anxiety Scale-Child, DSM-5 Depression Scale-Child.Results: The traditional bully, traditional victim, cyberbully and cyber victims or non-victims were compared, no statistically significant difference was found between demographic characteristics. When the effect of being a victim or a bully on DSM-5 Depression, DSM-5 Anxiety and APRS total scores were analyzed by linear logistic regression analysis, it was determined that being a traditional victim is a potential risk factor for increasing depression and anxiety and decreasing in resilience.Conclusion: Bullying exposure predicts psychiatric morbidity in the already difficult adolescence; therefore, prevention of this situation should be a priority in preventive public health.
Keywords: Adolescents; Bullying; Cyberbullying; Resilience; Victimization